Engineers at War. - Karlin, S.
The U.S. Department of Defense and the Army Corps of Engineers are still looking for a few good civilian engineers (go to http://www.cpol.army.mil). Although many of the contracts with private industry are winding down in Iraq, building in Afghanistan is ramping up. Washington Group International, an engineering, construction, and management firm in Boise, Idaho, is exploring possible projects in Afghanistan. The company has cut its employment in Iraq to 75 expatriate and 1000 Iraqi engineers from a high of 200 expats and 5000 Iraqis. (At press time, the San Francisco engineering firm URS was poised to purchase WGI.).
Keywords: Afghanistan; Army Corps of Engineers; Iraq; US Department of Defense; Washington Group International; Civilian engineers; Private industry